Ibulocydine sensitizes human hepatocellular carcinoma cells to TRAIL-induced apoptosis via calpain-mediated Bax cleavage. (February 2017) - Park, Seok Soon; Jwa, Eunjin; Shin, Seol Hwa; Ju, Eun Jin; Park, Intae; Pak, Jhang Ho; Hwang, Jung Jin; Cho, Dong-Hyung; Kim, B.Moon; Kim, Sung-Bae; Lee, Jung Shin; Song, Si Yeol; et al.
Abstract: Tumor necrosis factor-related apoptosis-induced ligand (TRAIL) induces apoptosis selectively in cancer cells without affecting the majority of normal human cells. However, hepatocellular carcinoma (HCC) cells often display resistance to TRAIL-induced apoptosis. Ibulocydine (IB) is an isobutyrate ester pro-drug of a novel synthetic Cdk inhibitor that targets Cdk7 and Cdk9. In this study, we show that treatment with subtoxic doses of IB in combination with TRAIL displays potent cytotoxicity in TRAIL-resistant human HCC cells. Combination of IB and TRAIL was found to synergistically induce apoptosis through activation of caspases, which was blocked by a pan-caspase inhibitor (zVAD). Although the expression of Mcl-1 and survivin were reduced by IB plus TRAIL, overexpression of Mcl-1 and survivin did not block the cell death induced by co-treatment. Moreover, overexpression of Bcl-xL did not significantly interfere with the cell death induced by co-treatment of IB and TRAIL. Interestingly, the combination treatment induced cleavage of Bax, which was translocated to mitochondria upon induction of apoptosis. Furthermore, down-regulation of Bax by small interfering RNA effectively reduced the cell death and loss of mitochondrial membrane potential (MMP) caused by co-treatment with IB and TRAIL. Finally, pre-treatment of HCC cells with a calpain inhibitor effectively blocked IB plus TRAIL-induced cleavage of Bax and apoptosis. Collectively, our results demonstrate that IB increases the sensitivity of human HCC cells to TRAIL via mitochondria signaling pathway mediated by calpain-induced cleavage of Bax, suggesting that combined treatment with IB and TRAIL may offer an effective therapeutic strategy for human HCC.